Factors that affect patient reported outcome after anterior cruciate ligament reconstruction–a systematic review of the Scandinavian knee ligament registers. Issue 7 (20th July 2018) - Hamrin Senorski, Eric; Svantesson, Eleonor; Baldari, Angelo; Ayeni, Olufemi R; Engebretsen, Lars; Franceschi, Francesco; Karlsson, Jón; Samuelsson, Kristian
Abstract : Objective: To perform a systematic review of findings from the Scandinavian knee ligament registers with regard to factors that affect patient reported outcome after anterior cruciate ligament (ACL) reconstruction. Design: Systematic review. Data sources: Four electronic databases: PubMed, EMBASE, the Cochrane Library and AMED were searched, and 157 studies were identified. Two reviewers independently screened the titles, abstracts and full text articles for eligibility. A modified version of the Downs and Black checklist was applied for quality appraisal. Eligibility criteria for selecting studies: Studies published from the Scandinavian registers from their establishment in 2004 and onwards that documented patient reported outcome and provided information on concomitant injuries were eligible. Results: A total of 35 studies were included. Younger age at ACL reconstruction, male sex, not smoking and receiving a hamstring tendon autograft positively influenced patient reported outcome. Patients with concomitant cartilage and meniscal injuries reported inferior subjective knee function compared with patients with an isolated ACL tear. One study reported that patients treated non-reconstructively reported inferior knee function compared with patients who had ACL reconstruction. Conclusion: Younger age, male sex, not smoking, receiving a hamstring tendon autograft and the absence of concomitant injuries were associated with superior patient reported outcomes after ACL reconstruction.